Mimicking Peroxidase Activity by a Manganese(II) Complex Involving a New Asymmetric Tetradentate Ligand Containing Both Amino and Imino Groups - Yolanda Pérez-Otero; M. Isabel Fernández-García; Esther Gómez-Fórneas; Gustavo González-Riopedre; Marcelino Maneiro (Journal of Chemistry)
The asymmetric ligand (E)-4-bromo-2-(((2-((5-bromo-2-hydroxybenzyl)(methyl)amino)ethyl)imino)methyl)phenol has been prepared by a novel seven-step route. All organic compounds isolated in each step have been characterised by elemental analysis, infrared and 1H NMR spectroscopy, and mass spectrometry. Interaction of this ligand with manganese has been investigated employing an electrochemical method. This method leads to the formation of a neutral manganese(II) complex 7 in high yield and purity. The complex has been thoroughly characterised by elemental analysis, infrared spectroscopy, mass spectrometry, magnetic susceptibility measurements, and cyclic voltammetry. Complex 7 behaves as peroxidase mimic in the presence of the water-soluble trap ABTS, probably due to its ease to coordinate the substrate molecule.